2012
DOI: 10.1111/j.1574-6941.2012.01476.x
|View full text |Cite
|
Sign up to set email alerts
|

Emission of nitrous oxide and dinitrogen by diverse earthworm families from Brazil and resolution of associated denitrifying and nitrate-dissimilating taxa

Abstract: The anoxic earthworm gut augments the activity of ingested microorganisms capable of anaerobiosis. Small earthworms (Lumbricidae) emit denitrification-derived N(2)O, whereas the large Octochaetus multiporus (Megascolecidae) does not. To examine this paradox, differently sized species of the families Glossoscolecidae (Rhinodrilus, Glossoscolex, Pontoscolex), Megascolecidae (Amynthas, Perionyx), Acanthodrilidae (Dichogaster), and Eudrilidae (Eudrilus) from Brazil were analyzed. Small species and the large Rhinod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 72 publications
1
18
0
Order By: Relevance
“…Experiments have repeatedly demonstrated that N 2 O emissions are associated with microbial processes happening in the gut19 and worm-worked soils37, where the populations of denitrifiers and dissimilatory nitrate reducers can be more abundant than in bulk soil18. Furthermore, the physical process of ingesting microbial cells might kill some of them, releasing N trapped in microbial biomass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments have repeatedly demonstrated that N 2 O emissions are associated with microbial processes happening in the gut19 and worm-worked soils37, where the populations of denitrifiers and dissimilatory nitrate reducers can be more abundant than in bulk soil18. Furthermore, the physical process of ingesting microbial cells might kill some of them, releasing N trapped in microbial biomass.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the in situ conditions of earthworm guts are likely to favor denitrification. N 2 O and N 2 emissions from earthworms and denitrification genes were reported to be enriched in the alimentary canal of earthworms19. Likewise, the products of metabolic processes happening in the gut can be released in the soil20212223 and benefit microbial communities living even beyond the drilosphere24.…”
mentioning
confidence: 99%
“…The in situ conditions of the gut stimulate ingested obligate anaerobes and facultative aerobes that promote diverse fermentations along the alimentary canal, and fermentation-derived molecular hydrogen (H 2 ) is emitted in vivo by earthworms (Karsten and Drake, 1995;Schmidt et al, 2001;Wü st et al, 2009aWü st et al, , 2011. Fermentation products in the gut may serve as substrates for soil-derived denitrifiers and be trophically linked to the in vivo emission of nitrous oxide (N 2 O) and dinitrogen (N 2 ) (Karsten and Drake, 1997;Matthies et al, 1999;Depkat-Jakob et al, 2013). In this regard, earthworms can contribute to the capacity of soils to emit nitrogenous gases (Karsten and Drake, 1997;Matthies et al, 1999;Rizhiya et al, 2007;Lubbers et al, 2011), and it has been postulated that the emission of H 2 by earthworms might drive energy-dependent processes in soil such as the fixation of N 2 or carbon dioxide (CO 2 ) (Wü st et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…The N 2 O concentrations in the gut of Aporrectodea caliginosa and Lumbricus rubellus ranged from 0.2 to 17.6 μM . Amynthas gracilis and Pontoscolex corethrurus led to 10.7 and 11.6 nmol N 2 O g (fresh weight) −1 emissions from a grassland soil (Depkat-Jakob et al 2013). In a mesocosm study using a sandy soil, Giannopoulos et al (2011) found that L. rubellus increased cumulative N 2 O emission from 228 to 859 μg N 2 O-N kg −1 after 90 days.…”
Section: Introductionmentioning
confidence: 97%
“…Bertora et al (2007) reported that the incorporation of Aporrectodea longa into soil increased N 2 O emission by approximately 30 % from 3 to 12 days. It has been suggested that earthworms themselves, their casts, and drilosphere can be a source of N 2 O emissions and that earthworm-induced N 2 O emissions are mainly due to the enhanced nitrification in soil Karsten and Drake 1997;Elliott et al 1991) and denitrification in earthworm gut (Depkat-Jakob et al 2013;Majeed et al 2013). According to Giannopoulos et al (2011), earthworm-induced N 2 O emission may be due to the earthworms' stimulation of microbial activity and/or changes in the microbial community composition.…”
Section: Introductionmentioning
confidence: 99%